Mental Disorders, Comorbidity, and Pre‐enlistment Suicidal Behavior Among New Soldiers in the U.S. Army: Results from the Army Study to Assess Risk and Resilience in Servicemembers (Army STARRS). Issue 5 (26th January 2015) - Nock, Matthew K.; Ursano, Robert J.; Heeringa, Steven G.; Stein, Murray B.; Jain, Sonia; Raman, Rema; Sun, Xiaoying; Chiu, Wai Tat; Colpe, Lisa J.; Fullerton, Carol S.; Gilman, Stephen E.; Hwang, Irving; et al.
<x xml:space="preserve">Abstract</x> We examined the associations between mental disorders and suicidal behavior (ideation, plans, and attempts) among new soldiers using data from the New Soldier Study (NSS) component of the Army Study to Assess Risk and Resilience in Servicemembers (Army STARRS; N = 38, 507). Most new soldiers with a pre‐enlistment history of suicide attempt reported a prior mental disorder (59.0%). Each disorder examined was associated with increased odds of suicidal behavior (ORs = 2.6–8.6). Only PTSD and disorders characterized by irritability and impulsive/aggressive behavior (i.e., bipolar disorder, conduct disorder, oppositional defiant disorder, and attention‐deficit/hyperactivity disorder) predicted unplanned attempts among ideators. Mental disorders are important predictors of pre‐enlistment suicidal behavior among new soldiers and should figure prominently in suicide screening and prevention efforts.